New taxa and records of Phaneropterinae (Orthoptera: Tettigoniidae) from China - Liu, Chun-Xiang; Kang, Le (Zootaxa, 2007)
Two new genera, Semicarinata gen. nov., and Qinlingea gen. nov., are described from China, with description of one new species, S. colorata sp. nov., and one new combination, Q. brachystylata (Liu and Wang, 1998). Two species, i.e., Tamdaopteron major Gorochov, 2005, and Indogneta lata Ingrisch and Shishodia, 2000, as well as these two genera, are first records for China. We also gave additional descriptions about male stridulatory area of these two genera and the first female description of the species I. lata. A key to the genera with open tympana in China is provided.